Flame propagation of premixed gas mixtures deflagration in tee pipelines / Sina Davazdah Emami - Sina Davazdah , Emami (2016)
Explosions in chemical, gas and petroleum industries are still a significant problem leading to injuries, death, destruction of equipment and downtime. In the chemical, hydrocarbon and gas process industries, a large variety of cases can be found where internal gas explosions, confined explosion, may occur. As a consequence there is a need to protect gas pipelines against propagation of unwanted combustion phenomena such as deflagrations to detonations transmission (DDT). However, a review of the literatures revealed that flame acceleration of hydrocarbons/air, hydrogen/air, hydrocarbonshydrogen/ air and hydrogen-inhibitors/air mixtures with wild range of concentration in tee pipelines are still unclear. Thus, given the gaps in the literature, this research was carried out to investigate the dynamics of flame propagation of premixed gas mixtures deflagration in tee pipelines for determining the most critical point(s) of tee pipelines based on the rate of pressure rise with respecting ignition positions. In this research study, the fuel/air mixtures were ignited at six different ignition positions in two different tee pipes’ configuration. The results of pure hydrocarbons/air and hydrogen/air mixtures show that, while there is no significant difference in the maximum pressure and rate of pressure rise in both the tee-pipe arrangements investigated, the bending pipe consistently produces the worst set of results in terms of maximum pressure and flame speeds, in pipe explosions involving the most reactive mixtures. In addition, the detailed records of pressure traces and blast waves show that the duration of flame acceleration, the flame direction and the initial ignition point depend on the tee junction placement along the pipe length, as this gives a different overall profile of the flame acceleration mechanism. Moreover, for the overall observation of hydrocarbons-hydrogen/air mixture, it can be said that the flame reactivity of ethylene-hydrogen/air and NG-hydrogen/air was much higher. The kinetic reaction of these mixtures contributed to the overall explosion development. However, the dynamics of flame deployment in the tee junctions had a significant effect on the recorded maximum overpressure and flame speeds along the pipes. The obtained data show that the lower distance between tee junction and the ignition point caused a higher explosion severity in terms of the rate of pressure rise. The results show that, when ignited at the furthest distance, the tee junction area is most vulnerable to the critical pressure impact of gas explosion. However, no similar trend was observed at the other ignition positions. In addition, mixtures with compositions of 95% H2-2.5% Ar-2.5% N2/air, 95% H2-5% N2/air, H2/air and 95% H2-5% Ar/air showed the highest risks due to the higher diffusivity ratio and the associated rate of pressure rise. The results show that mixtures with CO2 lead to lower severity than other hydrogeninhibitors/ air mixutures (~ 50% reduction), as the average recorded maximum flame speed for this particular mixture was lower at all of the ignition points. This suggests that the effectiveness of the inhibitors should be in the order of Ar < N2 < CO2.